Enhancing English Vocabulary Learning for Children with Special Needs Using a Differentiated Method - Hidayati, Dian Alina; Amalia, Taranindya Zulhi (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2025)
Language is a fundamental communication tool that enables interaction across various contexts. As a global lingua franca, English can be introduced to children at an early age, including those with special needs. This study explores the effectiveness of a differentiated learning approach in enhancing English vocabulary acquisition among children with special needs. Employing an action research design, the study was conducted in three cycles, each comprising planning, action, observation, and reflection. Data were collected through observations and vocabulary tests administered over the three cycles. In the first cycle, visual media such as flashcards were used to introduce vocabulary. The second cycle incorporated auditory learning through songs, while the third cycle integrated audiovisual media in the form of animations. Five early childhood education (ECE) students with special needs participated in the study. Findings revealed that differentiated instruction significantly improved vocabulary acquisition. The students’ average vocabulary test scores increased from 45 in the first cycle to 35 in the second, before reaching 75 in the third cycle. These results highlight the efficacy of differentiated learning strategies in addressing the diverse needs of children with special needs, providing an inclusive and adaptive approach to vocabulary instruction. The study underscores the importance of employing multimodal instructional techniques to enhance language acquisition and suggests that differentiated methods can serve as a valuable pedagogical tool for educators working with special needs learners. Future research may explore long-term retention and the impact of differentiated learning on other language skills.